Variation of endothelium‐related hemostatic factors during sepsis. (10th October 2018) - Vasileiadis, Ioannis; Politou, Marianna; Dimopoulos, Stavros; Rovina, Nikoletta; Kyriakopoulou, Magdalini; Kyriakoudi, Anna; Tripodaki, Elli‐Sophia; Koutsouri, Theodora; Terpos, Evangelos; Koulouris, Nikolaos; Koutsoukou, Antonia
Abstract: Objective: The thrombomodulin/protein C and VWF/ADAMTS‐13 pathways are disturbed in sepsis and have been implicated in the coagulation disorders that characterize the septic syndrome. We aimed to assess the variation of these endothelial parameters during sepsis and their putative association with outcome, in critically ill, septic patients. Methods: We monitored 34 septic patients, 23 of whom improved (group A) while 11 deteriorated (group B). We assessed ADAMTS‐13 levels, VWF activity, soluble thrombomodulin, and protein C activity upon admission to the ICU (time point 0) and at the time of a change in the clinical condition (remission or deterioration, time point 1). Results: In group A, thrombomodulin and VWF increased at time point 1 compared to time point 0 ( P  = 0.011, P  = 0.028, respectively). In group B, protein C and ADAMTS‐13 significantly decreased ( P  = 0.023, P  = 0.026, respectively), while VWF, VWF/ADAMTS‐13 ratio, and the thrombomodulin/protein C ratio increased ( P  = 0.02, P  = 0.002, P  = 0.01, respectively). Protein C (> or ≤17%) and ADAMTS‐13 percentage difference (> or ≤22%) were independently associated with sepsis outcome among the endothelial variables tested. Conclusions: An ongoing endothelial/hemostatic disorder was established during sepsis, observed even at clinical improvement. Among the variables tested, protein C and ADAMTS‐13 change were associated with outcome.